New muslims' experience in embracing Islam - Nuradli Ridzwan Shah M.D.; Azman Ab.R.; Irwan M.S.; Wan Mohd Fazrul Azdi W.R.; Rose Irnawaty I.N.; Mahazan Abdul Mutalib @ Talib (Islamic Cultural Centre, 2024)
New Muslims have to go through three different phases in the course of embracing Islam. The three phases are pre-conversion, conversion and post-conversion. The purpose of this paper is to seek understanding of what the new Muslims have to go through in embracing Islam. Focus groups and surveys were conducted to reveal the phenomena new Muslims encountered when embracing Islam.